Global Sustainable Development Report 2023 - United Nations Department of Economic; Social Affairs (United Nations, 2023)
Authored by an independent group of scientists appointed by the United Nations Secretary-General, the Global Sustainable Development Report 2023 presents a science-based call for transformations to achieve the 2030 Agenda. The authors analyze the phases of transformation, including emergence, acceleration and stabilization, and offer recommendations on how to achieve these phases in a range of sectors. The authors also present recommendations on making science itself more fit for purpose to achieve sustainable development.